Rede híbrida de distribuição de energia em CC e CA como solução alternativa para microrredes isoladas - Oliveira, Hércules Araújo (2017)
This work proposes a topology of isolated microgrids with hybrid network (part in DC and part in AC) of electric power distribution. This topology can serve as an alternative model to the conventional AC distribution network model for the electrical service of isolated communities. The topology consists of using a main system of DC power distribution and subsystems with an AC distribution. DC/AC converters are strategically distributed along the DC main network, forming AC subsystems, in order to serve a certain number of consumers with AC loads. Although there are loads that can be fed in DC, this is not a reality for household loads, which are basically AC powered. Thus, the interest of this work is to evaluate the possible advantages of this topology over the conventional microrredes with distribution network in low voltage in AC. In this contexto, the analysis parameters to be studied are: the increasing the extension of the distribution network without the need to use transformers, electric conductors with larger cross sections or distributed generation; the efficiency in the distribution of energy, evaluating the losses, and the reduction of implantation and operation costs. In order to compare the microgrid with hybrid distribution network, an isolated microgrid with purely CA distribution network was adopted as reference: the microgrid with solar-wind generation of Lençóis Island, located in the northeast of Brazil, which has been in operation since July 2008.